Reforming the Gazettment of State Forest Area in Riau Province - Pernando Sinabutar; Bramasto Nugroho; Hariadi Kartodihardjo; Dudung Darusman (Institut Pertanian Bogor (IPB University), 2014)
Controlling and determining ownership of forest area in Indonesia are done by units of forest area gazettment, which are ranging from designation to determination of boundary. The process is not quite easy and have tendency to be unsuccessful. The aim of study was to reveal the difficulty and to analyze series of measurements to reform. Descriptive data were analyzed qualitatively using strategy typology based on data collected through in-depth interviews, participant observation and document review. The results showed that forest area gazettments had not been able to guarantee tenure as proof of ownership at local level dominated by proven un-written rights. Delineation process had potential conflict because it did not disclose claims process in a transparent manner. The mechanism of strengthening forest area did not meet the rules. This is because of low capability of Forest Boundary Committee (PTB). Therefore, it requires a set of actions namely strengthening of the PTB, separating duties between achievement and maintenance of legitimacy. To maintain the legitimacy needs the presence of managers at site levelwith strong legitimacy from government to collaborate with non-governmental organizations.